Removal of micropollutants through a biological wastewater treatment plant in a subtropical climate, Queensland-Australia. Issue 1 (December 2016) - Cardenas, Miguel; Ali, Imtiaj; Lai, Foon; Dawes, Les; Thier, Ricarda; Rajapakse, Jay
Abstract Background Municipal wastewaters contain a multitude of organic compounds derived from domestic and industrial sources including active components of pharmaceutical and personal care products and compounds used in agriculture, such as pesticides, or food processing such as artificial sweeteners often referred to as micropollutants. Some of these compounds or their degradation products may have detrimental effects on the environment, wildlife and humans. Acesuflame is one of the most popular artificial sweeteners to date used in foodstuffs. The main objectives of this descriptive study were to evaluate the presence of micropollutants in both the influent and effluent of a large-scale conventional biological wastewater treatment plant (WWTP) in South-East Queensland receiving wastewater from households, hospitals and various industries. Methods Based on USEPA Method 1694: Filtered samples were spiked with mass-labelled chemical standards and then analysed for the micropollutants using liquid chromatography coupled with tandem mass spectrometry. Results The presence of thirty-eight compounds were detected in the wastewater influent to the treatment plant while nine of the compounds in the categories of analgesic, anti-inflammatory, alkaloid and lipid/cholesterol lowering drugs were undetectable (100 % removed) in the effluent. They were:Analgesic : Paracetamol, Salicylic acid, Oxycodone;Anti -inflammatory : Naproxen + ve, Atorvastatin, Indomethacin, Naproxen;Alkaloid : Caffeine;Lipid /cholesterol lowering : Gemfibrozol. Conclusions The study results revealed that the micropollutants removal through this biological treatment process was similar to previous research reported from other countries including Europe the Americas and Asia, except for acesulfame, a highly persistent artificial sweetener. Surprisingly, acesulfame was diminished to a much greater extent (>90 %) than previously reported research for this type of WWTPs (45–65 %) that only include physical removal of objects and solids and a biodegradation step.